Mitral Regurgitation: Anatomy, Physiology, and Pathophysiology—Lessons Learned From Surgery and Cardiac Imaging - Topilsky, Yan (Frontiers in Cardiovascular Medicine, 2020)
The normal mitral valve is a dynamic structure that permits blood to flow from the left atrial (LA) to left ventricle (LV) during diastole and sealing of the LA from the LV during systole. The main components of the mitral apparatus are the mitral annulus (MA), the mitral leaflets, the chordae tendineae, and the papillary muscles (PM) (Figure 1). Normal valve function is dependent on the integrity and normal interplay of these components. Abnormal function of any one of the components, or their interplay can result in mitral regurgitation (MR). Understanding the anatomy and physiology of all the component of the mitral valve is important for the diagnosis, and for optimal planning of repair procedures. In this review we will focus first on normal anatomy and physiology of the different parts of the mitral valve (MA, leaflets, chordae tendineae, and PM). In the second part we will focus on the pathologic anatomic and physiologic derangements associated with different types of MR.